Respuesta :
Answer:
h'(5) = ⅔
Step-by-step explanation:
I assume you mean h(x) = √(3 + 2f(x)).
Taking derivative using chain rule:
h'(x) = ½ (3 + 2f(x))^-½ · 2f'(x)
h'(x) = f'(x) / √(3 + 2f(x))
h'(5) = f'(5) / √(3 + 2f(5))
h'(5) = 2 / √(3 + 2 · 3)
h'(5) = ⅔
Chain rule of differentiation is used to find the derivative of composite functions
[tex]h'(5) = \dfrac{2}{3}[/tex]
Reason:
Given function:
Correction [tex]h(x) = \sqrt{3 + 2 \cdot f(x)}[/tex]
f(5) = 3
f'(5) = 2
By chain rule of differentiation, we have;
[tex]\dfrac{dy}{dx} =\dfrac{dy}{du} \cdot \dfrac{du}{dx}[/tex]
Therefore;
[tex]h'(x) = \dfrac{1}{2} \times (3 + 2 \cdot f(x))^{\frac{1}{2} -1} \times 2\cdot f'(x) = \dfrac{2\cdot f'(x) }{2\times \sqrt{3 + 2 \cdot f(x)} }[/tex]
[tex]h'(x) = \dfrac{f'(x) }{ \sqrt{3 + 2 \cdot f(x)} }[/tex]
[tex]h'(5) = \dfrac{2 }{ \sqrt{3 + 2\times 3 } } = \dfrac{2}{3}[/tex]
[tex]h'(5) = \dfrac{2}{3}[/tex]
Learn more about chain rule of differentiation here:
https://brainly.com/question/11549233